A formalized safety system for closed-loop anesthesia with pharmacokinetic and pharmacodynamic constraints. (March 2019) - Yousefi, Mahdi; van Heusden, Klaske; West, Nicholas; Mitchell, Ian M.; Ansermino, J. Mark; Dumont, Guy A.
Abstract: Closed-loop anesthesia drug delivery systems can reduce the effect of inter-patient variability, minimize variability in desired clinical effects, and ultimately improve patient safety. Feasibility of closed-loop anesthesia has been clinically evaluated in a number of studies. To obtain regulatory approval to use closed-loop anesthesia as a clinical device, patient safety must be demonstrated. Safety systems for closed-loop anesthesia have been proposed to limit anesthetic concentrations in the plasma and effect-site. Such safety systems minimize the risk of drug under/overdosing. Anesthetic drugs have serious side effects and can significantly reduce blood pressure, thereby jeopardizing patient safety. This paper discusses a safety system that includes safety constraints on blood pressure in addition to the plasma and effect-site concentrations. The proposed safety system is formalized using formal model verification techniques. The performance of closed-loop anesthesia in the presence of constraints on the plasma and effect-site concentrations as well as blood pressure is shown using simulation results. The effectiveness of the proposed safety system is also illustrated in simulation using a realistic clinical scenario. This paper shows that maintaining blood pressure within safety constraints increases the time for anesthesia induction, especially for patients whose blood pressure is more sensitive to anesthetics. For this population, clinical intervention such as administration of vasoactive drugs may be required to counter the effect of propofol on blood pressure during closed-loop anesthesia to achieve a safe yet sufficiently fast induction. This paper extends a previously published formalized safety system which guarantees that the plasma and effect-site concentrations remain within safety limits (Yousefi et al., 2017). Highlights: A formal proof of safety for closed-loop propofol anesthesia is provided. Closed-loop anesthesia can be performed with minimum risk of drug over/under dosing and hypotension. Limiting blood pressure increases the induction time of anesthesia. Administration of vasoactive drugs may be required to have a fast induction of anesthesia while avoiding hypotension.